PERAN, TUGAS DAN FUNGSI ORANG TUA DALAM PENDIDIKAN: Studi Al–Qur’an Surat At–Tahrim Ayat 6 dan Luqman Ayat 13 - fitriyani nurfitroh (Al-Fath, 2024)
The important role of parents when educating children physically and mentally. In the Islamic context, the Koran provides clear instructions regarding the duties and functions of parents in the education of their children. These two verses, At-Tahrim verse 6 and Luqman verse 13, emphasize the role, responsibility and function of parents in guiding their children. This article aims to explore this concept and its relevance to modern education from a Quranic perspective. Through analysis of these two verses, this article explores the role of parents as spiritual guides, their responsibility for the religious, moral and physical education of their children, as well as as role models, supporters and guides. This article also highlights the relevance of these concepts in the context of inclusive education and parent-school collaboration. Therefore, this article examines the important role of parents in giving birth to a quality generation based on the teachings of the Koran.